An Operator Method for a Third Order Partial Differential Equation. (3rd October 2017) - Ashyralyev, Allaberen; Simsek, Sinem N.
ABSTRACT: In this study, the nonlocal boundary value problem for the third order partial differential equation with a self-adjoint positive definite operator in a Hilbert space is investigated. The main theorem on stability estimates for the solution of the problem is established. The application of the main theorem for two types of third order partial differential equations is provided.